Numerical simulation of a sinking ship scenario based on archaeological records (Archaeologia Adriatica, 2021)
Over the past decade, photogrammetric recording and virtual 3D modelling have evolved as a standard practice in documenting shipwreck sites. Exploiting the same methods, we can attempt to virtually reconstruct the dynamics of an accident leading to the creation of an archaeological site. By applying modern engineering tools capable of deploying multi-body system dynamics to simulate the damaging, capsizing and/or sinking of a ship, we can model and analyse the various possible scenarios of an incident occurring to an ancient merchantman. Subsequently, we can establish the correlation between the characteristics of the actual shipwreck site, and the outcome of the numerical simulation of the assumed scenario.
Keywords: ship; shipwreck scenario; numerical modelling; simulation; amphorae; virtual reconstruction